Nonfatal Suicidal Overdose of Olanzapine in an Adolescent - Kumar Singh, Lokesh; Kumar Praharaj, Samir; Sahu, Manoj (Current Drug Safety, 2012)
The atypical antipsychotic olanzapine is increasingly being used for various psychiatric conditions. There are few reports of olanzapine overdose in adolescent population. We report a case of 16-year-old adolescent who ingested 750 mg olanzapine, the highest reported nonlethal dose of olanzapine in adolescents. He presented with tachycardia, hypotension, generalized myoclonus, hyperpyrexia, muscular rigidity, leukocytosis and elevated creatine phosphokinase (CPK) levels. He recovered from the toxicity with minimal intervention.
Keywords: overdose